Hydrological modelling for sustainable rural and urban landscapes in Latvia - Bakute, Anda; Grinfelde, Inga; Groosman, Marcel (Landscape Architecture and Art, 2025)
Effective landscape planning requires a comprehensive understanding of how land use affects hydrological processes - especially in regions such as Latvia, where climate change, urbanisation, and fragmented hydrological data complicate decision-making. This study applies the METQ conceptual rainfall–runoff model to three representative Latvian catchments (Iecava, Pērse, and Imula), each characterised by differing forest, agricultural, and urban land use patterns. Using long-term hydrometeorological data and detailed land cover classifications, the model was calibrated and validated to simulate daily runoff dynamics and explore the influence of land use on flood risk and water balance. Results indicate that forested and semi-natural areas attenuate peak flows and enhance baseflow retention, while intensively cultivated and urbanised landscapes increase surface runoff and flood potential. Scenario simulations further reveal that even small increases in impervious area can significantly elevate peak discharge, whereas the implementation of green infrastructure can mitigate these effects. The study demonstrates that METQ provides reliable, spatially explicit hydrological insights that support sustainable land use planning, particularly in data-scarce contexts. The findings emphasise the importance of incorporating hydrological models into spatial planning and environmental assessment processes. Such integration allows planners and designers to visualise the consequences of development decisions, evaluate alternative land use configurations, and enhance landscape resilience in the face of climate change. The approach presented here offers a transferable model for landscape planning in other Baltic and Northern European regions facing similar socio-environmental challenges.